Effects of betaine supplementation on muscle strength and power: A systematic review - Ismaeel, A. (The Journal of Strength and Conditioning Research, 2017)
Betaine (BET) has recently gotten much attention for its potential role as an ergogenic aid and has become a common ingredient in peri-workout dietary supplements. The purpose of this systematic review of the literature was to investigate the effects of BET supplementation on muscular strength and power. A computerized literature search of 3 databases (PubMed, MEDLINE, and Scopus) was performed. Included in the review were randomized controlled trials that measured muscle strength, power, or both measures in healthy participants. Quality was assessed using the PEDro scale. Seven trials were identified, and quality assessment showed that all were of "excellent quality." Only 2 of the studies reported increases in strength or power after supplementation with BET. The remaining 5 studies showed no change in any strength or power outcome measures with BET supplementation. This review highlights the lack of evidence for a clear ergogenic effect of BET supplementation on strength and power performance. However, because 2 studies did identify increases of up to 24.61% on strength and power as a result of BET supplementation, additional studies are necessary to evaluate its effectiveness.